Vibration of rigid bodies in the visco-elastic Hook-Maxwell model - Nguyen Van Dao (Vietnam Journal of Mechanics)
In this paper the self-excited and forced vibrations of rigid bodies fastened to visco-elastic beam are considered. Two parameters solutions of motion equations of third order are found in the asymptotic series and their stability is investigated. It was shown that in comparison with Hook material the Hook-Maxwell material of beam limits the growth of amplitudes of both self-excited and forced vibrations. The theoretical results agree well with experimental ones.